Pengaruh Kepemimpinan dan Kompetensi Terhadap Kinerja Pegawai Melalui Motivasi Sebagai Variabel Intervening - Firmansya, Randi; Ronal Aprianto; Fitria, Fitria (MAMEN: Jurnal Manajemen, 2022)
The purpose of this study was to determine the effect of leadership and competence on employee performance through motivation as an intervening variable at the Department of Population Administration and Civil Registration Office of North Musi Rawas Regency. The population and research sample amounted to 39 employees. Methods of data analysis using quantitative analysis. The results showed that leadership has an effect on employee performance with a value of tcount = 5.583 > ttable = 1.685, significant 0.000 <0.05. Competence has an effect on employee performance with a value of tcount = 4.675 > ttable = 1.685, significant 0.000 <0.05. Motivation has an effect on employee performance with a value of tcount = 5.122 > ttable = 1.685, significant 0.000 <0.05. Leadership and Competence have an effect on motivation with Fcount = 10.210 > Ftable = 3.26, significant 0.000 <0.05. Leadership and Competence affect employee performance with a value of Fcount = 29.773 > Ftable = 3.26, significant 0.000 <0.05. Leadership has an effect on employee performance through motivation as an intervening variable with a value of tcount = 2.286 > ttable = 1.685. Competence affects employee performance through motivation as an intervening variable with a value of tcount = 1,947 > ttable = 1,685. The conclusion is that leadership and competence affect employee performance through motivation as an intervening variable at the Department of Population Administration and Civil Registration Office of North Musi Rawas Regency.